Rags to Riches: One Migrant Worker's Journey to Educational Triumph - Sarah E. Broman (Educational Considerations, 2019)
The effect poverty has on a child’s education is tragic. Without the necessary life-sustaining resources, many of our nation’s children struggle to concentrate on anything other than their immediate dire circumstances. This article tells the story of how one migrant farm worker overcame her struggles living in abject poverty to become a first generation college student and future elementary education teacher thanks to her supportive family and her compassionate, caring educators along the way.
Keywords: poverty and literacy; first generation college student; teacher relationships; migrant worker